INTEGRATING ELECTRIC VEHICLES INTO SMART GRID USING IEC 61850 AND ISO/IEC 15118 STANDARDS - Gasto, Adore Lameck (My University, 2016)
The development of Electric Vehicle (EV) technology is evolving quickly due to the worlds growing concerns in environmental protection and energy conservation. The world is struggling to minimize CO2 emissions and fossil fuel dependency in transportation sector. Standardized communication interface is a key factor for the successful integration of electric vehicle into smart grid, interoperability of charging infrastructure and mass-market acceptance of E-Mobility. The deployment of the electric vehicle in large scale would be one of the feasible solutions because of its economical and environmentally friendly features. However, large deployment of the electric vehicle arises challenges at the grid level such as peak load impacts and charging control. Therefore, it is very crucial to investigate how to integrate electric vehicle into smart grid so that to avoid these effects. This thesis describes how the vehicle-to-grid communication interface (V2G CI) currently being developed in ISO/IEC 15118 can be connect to IEC 61850-7-420 standard for Distributed Energy Resources (DER). The client-server application is implemented to simulate EV charging process according to the ISO/IEC 15118 standard. Also the new logical nodes for monitoring and controlling EV and Electric Vehicle Supply Equipment (EVSE) are implemented for the simulation of the concept.
Keywords: Electric Vehicles; Electric Vehicle Supply Equipment; Smart Grid; Vehicle-to-Grid; ISO/IEC 15118; IEC 61850; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|